Low-dose amitriptyline for irritable bowel syndrome: a qualitative study of patients' and GPs' views and experiences - Teasdale, Emma J; Everitt, Hazel A; Alderson, Sarah L; Ford, Alexander C; Hanney, James; Chaddock, Matthew; Williamson, Emmajane; Cook, Heather; Farrin, Amanda J; Fernandez, Catherine; Guthrie, Elspeth A; Hartley, Suzanne; et al. (British journal of general practice, 2025)
Irritable bowel syndrome (IBS) can cause troublesome symptoms, which impact patients' quality of life and incur considerable health service resource use. Guidelines suggest low-dose amitriptyline for IBS as second-line treatment, but this is rarely prescribed in primary care. To explore patients' and GPs' views and experiences of using low-dose amitriptyline for IBS. Qualitative interview study with patients and GPs in England, nested within the ATLANTIS trial of low-dose amitriptyline versus placebo (ISRCTN48075063). Semi-structured telephone interviews were conducted with 42 patients at 6 months post-randomisation, with 19 patients again at 12 months post-randomisation, and with 16 GPs between April 2020 and March 2022. Reflexive thematic analysis was used to analyse patient and GP data separately, then together, to identify unique and cross-cutting themes. We found concerns about amitriptyline being an antidepressant, medicalising IBS, and side effects. Perceived benefits included the low and flexible dose, ease of treatment, and familiarity of amitriptyline and its potential to offer benefits beyond IBS symptom relief. These concerns and perceived benefits were expressed in the context of desire for a novel approach to IBS: GPs were keen to offer more options for IBS and patients sought a cure for their symptoms. Patients and GPs felt that the potential benefits of trying low-dose amitriptyline for IBS outweighed their concerns. When offering low-dose amitriptyline for IBS, GPs could address patient concerns about taking an antidepressant for IBS, highlighting the low and flexible dosage, and other potential benefits of amitriptyline such as improved sleep.